A Comparative Analysis of Multiatribute Fishbein Consumers of Pandan Wangi, Mentik Susu and Mentik Wangi Rice in Ngawi District - Mar'atus Sholihah, Elis Rahmawati; Nadhifah, Fairuz; Atmojo, Titin Andriyani (Westscience Press, 2025)
Rice serves as the staple food in Indonesia, with premium varieties such as Pandan Wangi, Mentik Wangi, and Mentik Susu gaining increasing popularity due to their distinctive aroma, texture, and flavor profiles. Understanding consumer preferences for these varieties is crucial for producers, distributors, and policymakers to develop effective marketing strategies and support food security initiatives. This study analyzes consumer preferences for aromatic rice in Ngawi Regency, East Java, focusing on key attributes including taste, price, packaging size, and brand perception. The research employs a descriptive analysis method utilizing the Fishbein Multi-Attribute Model to evaluate consumer attitudes. Data were collected from 90 respondents in Ngawi Regency, evenly distributed across the three rice varieties, using purposive sampling techniques. The questionnaire measured consumer belief (bi) and importance (ei) scores for each attribute, with data analysis conducted using Microsoft Excel. Findings indicate that Mentik Wangi rice emerged as the most preferred variety, achieving the highest total attitude score (Ao) of 67.4, supported by superior ratings in taste (4.07), price (4.13), packaging size (4.18), and brand perception (4.10). Pandan Wangi rice scored highest in brand trust (4.08), while Mentik Susu rice excelled in taste attributes (3.92). These results align with previous research, confirming that sensory quality and economic factors significantly influence consumer choices. This study contributes to the understanding of consumer preferences for aromatic rice in Indonesia and provides practical recommendations for stakeholders regarding product development and marketing strategies. The research novelty lies in its comparative evaluation of consumer perceptions across three premium rice varieties, offering a comprehensive perspective on local market dynamics.